Electrical Characterization Of Carbon Nanotube As Gas Sensing Element - Mohd Yusof, Farah Aniza (2007)

(untitled)
Gas sensing is very important in order to detect dangerous gases like carbon dioxide, ammonia and acetylene, which are commonly used in industries as well as in medical applications. Carbon Nanotube is a promising candidate for gas sensing element because of their large surface area. Therefore, they offer excellent sensitivity and rapid response towards surface changes. This work aims to investigate carbon nanotubes as gas sensing element. The growth of carbon nanotube has been done using Chemical Vapor Deposition (CVD) technique. The physical and electrical characteristics of carbon nanotube have been characterized using microscopes and source measurement unit. Sensors were fabricated and the variations of electrical resistance upon the exposure of carbon dioxide, ammonia and acetylene gas have been investigated. The technique for growing carbon nanotubes that is called Floating Catalyst CVD has been used to produce grams of carbon nanotube. The temperature was set from 800oC to 900oC. For that range of temperature, grams of carbon nanotubes are produced in which the diameter is from 40 nm – 200nm and the length is in micrometer. The carbon nanotubes produced are found to have multi-layered wall in about 8nm thickness. The diameter, length and wall thickness have been measured using the Scanning Electron Microscope (SEM), Atomic Force Microscope (AFM) and Transmission Electron Microscope (TEM). The multi-layered wall indicates that the carbon nanotubes are Multi-Walled Carbon Nanotubes (MWNTs). Gas-sensing samples have been prepared in the forms of pellet and films. Upon exposure of carbon dioxide, ammonia and acetylene gas, the resistance of the samples increases from their steady state value. From the research, it was found that the sensor is sensitive to carbon dioxide, ammonia and acetylene gas. The sensor can be operated at room temperature with response time as fast as 0.1 to 1 second.